Associations between drug and alcohol use, smoking, and frailty among people with HIV across the United States in the current era of antiretroviral treatment. (1st November 2022) - Crane, Heidi M.; Ruderman, Stephanie A; Whitney, Bridget M; Nance, Robin M; Drumright, Lydia N.; Webel, Allison R.; Willig, Amanda L.; Saag, Michael S.; Christopoulos, Katerina; Greene, Meredith; Hahn, Andrew W.; Eron, Joseph J.; et al.
Abstract: Objective: To examine associations between frailty and drug, alcohol, and tobacco use among a large diverse cohort of people with HIV (PWH) in clinical care in the current era. Methods: PWH at 7 sites across the United States completed clinical assessments of patient-reported measures and outcomes between 2016 and 2019 as part of routine care including drug and alcohol use, smoking, and other domains. Frailty was assessed using 4 of the 5 components of the Fried frailty phenotype and PWH were categorized as not frail, pre-frail, or frail. Associations of substance use with frailty were assessed with multivariate Poisson regression. Results: Among 9336 PWH, 43% were not frail, 44% were prefrail, and 13% were frail. Frailty was more prevalent among women, older PWH, and those reporting current use of drugs or cigarettes. Current methamphetamine use (1.26: 95% CI 1.07–1.48), current (1.65: 95% CI 1.39–1.97) and former (1.21:95% CI 1.06–1.36) illicit opioid use, and former cocaine/crack use (1.17: 95% CI 1.01–1.35) were associated with greater risk of being frail in adjusted analyses. Current smoking was associated with a 61% higher risk of being frail vs. not frail (1.61: 95% CI 1.41–1.85) in adjusted analyses. Conclusions: We found a high prevalence of prefrailty and frailty among a nationally distributed cohort of PWH in care. This study identified distinct risk factors that may be associated with frailty among PWH, many of which, such as cigarette smoking and drug use, are potentially modifiable. Highlights: The prevalence of prefrailty and frailty are high among people with HIV (PWH) in clinical care. The prevalence of frailty and prefrailty were higher among women and older PWH. Methamphetamine and illicit opioid use are associated with higher frailty risk. Smoking cigarettes was associated with greater risk of being frail.